Fort Yukon, Chalkyitsik, & Venetie Biomass Boiler Feasibility Study - Greg Koontz, ME William A. Wall, PhD (Council of Athabaskan Tribal Governments, 2009)
The Council of Athabascan Tribal Governments (CATG) is a consortium of ten Gwich'in and Koyukon Athabascan tribes settled in 10 remote villages and are linked by the Yukon River System. The CATG mission is to maintain the Yukon Flats region as Indian Country by asserting traditional rights and taking responsibility for developing tribal technical capacity to manage the land and resources. It is the intent of CATG to explore and develop all opportunities for a renewable and self-sufficient energy program for each of the villages. CATG envisions utilization of forest resources both for construction and energy as one of the best long-term strategies for integrating the economic goals for the region as well as supporting the cultural and social issues. The intent for this feasibility project is to focus specifically on biomass utilization for heat, first, and for future electrical generation within the region, second. An initial determination has already been made regarding the importance of wood energy as a primary source of renewable energy to displace diesel fuel in the Yukon Flats region. A desktop study of other potential renewable resources was conducted in 2006.